A woman under the influence [videorecording (DVD)] - Cassavetes, John, 1929-1989; Falk, Peter, 1927-2011; Rowlands, Gena; Draper, Fred (The Criterion collection, 2008)
A drama detailing the emotional breakdown of a suburban housewife and how her family struggles to save her from herself.